Inverse identification of radiative properties of a multi-component media in MPA modeling of radiative transfer. (March 2016) - Kowsary, Farshad; Gholamian, Hamed; Ashjaee, Mehdi; Moghadassian, Behnam
Abstract: Inverse identification of the radiative properties of a two-component media based on multi-phase approach (MPA) formulation of the radiative transfer phenomenon is investigated. Packed bed of semitransparent spheres under a normal collimated laser beam is considered as the geometry of the mentioned problem. Discrete normal directional reflectance and transmittance of the packed bed is used as input data to the identification procedure. The sensitivity of these two parameters to radiative properties of the medium is studied first, followed by the inverse parameter estimation. The discrete ordinates method is used to solve the direct problem while interior trust region (ITRA) algorithm is utilized in the identification process. Results indicate the ability of the presented procedure to estimate the desired radiative properties of the medium within an acceptable error margin. Moreover, the effect of uncertainty of the normal directional reflectance and transmittance data on the accuracy of the estimated parameters is assessed.